2014
DOI: 10.3390/cancers6031553
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Aptamer Targets the PDZ-Binding Motif of the HPV16 E6 Oncoprotein

Abstract: Human papillomavirus 16 (HPV16) is a high-risk DNA tumour virus which is the primary causative agent of cervical cancer. Cell transformation arises from deregulated expression of the E6 and E7 oncogenes. E6 has been shown to bind a number of cellular proteins, including p53 and proteins containing a PDZ domain. This study reports the first RNA aptamers to E6. These have been employed as molecular tools to further investigate E6-p53 and E6-PDZ interactions. This study is focussed on two aptamers (termed F2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Belyaeva et al reported two RNA aptamers to E6, named F2 and F4, which induced apoptosis in cells derived from an HPV16-transformed cervical carcinoma. This aptamers were able to inhibit the interaction between E6 and PDZ1 from Magi1, with F2 being the most effective inhibitor, while none of them inhibited E6–p53 interaction or p53 degradation [121]. …”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…Belyaeva et al reported two RNA aptamers to E6, named F2 and F4, which induced apoptosis in cells derived from an HPV16-transformed cervical carcinoma. This aptamers were able to inhibit the interaction between E6 and PDZ1 from Magi1, with F2 being the most effective inhibitor, while none of them inhibited E6–p53 interaction or p53 degradation [121]. …”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…exceeds the C eff value observed for another dimeric ligand targeting the PSD-95 protein (100-fold affinity increase, C eff % 100 mm). [19] Being built from fragments of two proteins targeted by all hrm-HPV E6 proteins,t he chimera proved to be au niversal ligand for hrm-HPV E6 proteins.T his is as trong advantage over previously published E6 ligands,i ncluding small molecules, [20] antibodies, [21] peptides, [22] and RNAa ptamers, [23] which were all developed to target only one particular E6 protein (HPV16 E6). Since E6 is ah allmark of all HPVpositive tumors,the chimera can serve as adiagnostic tool for E6 capture followed by immunodetection, as demonstrated here (Figure 3e).…”
Section: Methodsmentioning
confidence: 99%
“…The aptamer interaction with PDZ domain was very specific and the interaction between E6 and p53 was not affected [53]. The same research group also isolated RNA aptamers against E7 oncoprotein that were able to disturb the E7-pRb interaction by targeting E7 for degradation and showed that one of them (A2) was able to inhibit cellular proliferation by inducing apoptosis in SiHa cervical carcinoma cells [54].…”
Section: Aptamers Against Hpvmentioning
confidence: 99%